2020
DOI: 10.1093/ofid/ofaa491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Modifies the Clinic Presentation of Cutaneous Leishmaniasis

Abstract: Background Cutaneous leishmaniasis (CL) caused by L. braziliensis is characterized by one or multiple well limited ulcerated lesions. Diabetes mellitus (DM) impair neutrophil and monocyte function and there is a report of a vegetative lesions in a patient with both diseases in Morocco. Here we evaluate the influence of DM on clinical manifestations, immune response and in the treatment of CL. Methods Participants were 36 DM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Por otro lado, el uso de metrotexato o antagonista de factor de necrosis tumoral alfa como el infliximab y etarnecept se ha asociado a numerosos casos de leishmaniasis 5 . Cabe destacar también que los pacientes con diabetes mellitus tienen un mayor riesgo de leishmaniasis visceral y pueden enfrentar una curación más baja y tasas de recaída más altas, así como lesiones cutáneas atípicas en leishmaniasis cutánea 6,7 .…”
Section: Discussionunclassified
“…Por otro lado, el uso de metrotexato o antagonista de factor de necrosis tumoral alfa como el infliximab y etarnecept se ha asociado a numerosos casos de leishmaniasis 5 . Cabe destacar también que los pacientes con diabetes mellitus tienen un mayor riesgo de leishmaniasis visceral y pueden enfrentar una curación más baja y tasas de recaída más altas, así como lesiones cutáneas atípicas en leishmaniasis cutánea 6,7 .…”
Section: Discussionunclassified
“…Individuals with chronic HBV infection or anti-HBc positivity may have an increased risk of diabetes, and the association may be modified by the different statuses of metabolism-related variables and age[ 60 ]. DM modifies the clinical presentation of cutaneous leishmaniasis, enhances proinflammatory cytokine production, and impairs the response to antimony therapy[ 61 ]. To date, few studies have focused on the effects of cancer pathways, the thyroid hormone signaling pathway, pertussis, and proteoglycans in cancer on DM.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, metabolic diseases have been considered to increase one's susceptibility to infections, especially diabetes and obesity. 19,20 Diabetes mellitus has also been associated with a more severe clinical presentation and worse response to therapy of cutaneous leishmaniasis (CL), 21 and a case report showed an association between diabetes and VL. 22 Sernaglia et al 23 demonstrated that diet-induced obesity promotes systemic inflammation and increases susceptibility to murine visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%